Differentiation of Malaysian farmed and commercialised edible bird's nests through nutritional composition analysis - Zulkifli, Danish Adli; Mansor, Rozaihan; Md. Ajat, Mohd Mokrish; Abas, Faridah; Ideris, Aini; Abu, Jalila (Universiti Putra Malaysia Press, 2019)
The growing demand of edible bird’s nest (EBN) worldwide as well as competition from neighbouring countries has made the EBN industry one of the rising industries in Malaysia with stringent exportation requirement by China. However, as majority of the EBN products in the market is in commercialised form, studies on the nutritional composition of these commercialised EBN in comparison with farmed, raw EBN are limited. The farmed EBN samples were taken from 4 different regions of Malaysia: Perak (central), Kelantan (eastern), Johor (southern) and Sarawak (west Borneo) while the commercialised sample was obtained from a local drug store. Proximate, amino acid and elemental composition were performed on these EBNs. Farmed EBNs mainly comprised protein followed by carbohydrate while the commercialised EBN had similar protein and carbohydrate composition. The total collection of essential amino acid in commercialised EBN was higher (237.9 mg/g protein) compared to the farmed EBN which was between 156.81 − 236.6 mg amino acid/g protein. Among the essential amino acids, valine was found to be highest in both commercialised and farmed EBN. The differences between the nutritional compositions of EBNs could be due to the process of commercialisation of the EBN as well as seasonal, breeding sites and diet of the swiftlets. Farmed EBN therefore can be considered to be more nutritional due to higher protein levels.